Corpus-based approaches to English language teaching - Campoy Cubillo, Ma Carmen (Mari Carmen); Bellés Fortuño, Begoña; Gea Valor, M. Lluïsa (Corpus and discourse. Research in corpus and discourse., 2010)
Corpus-Based Approaches to ELT presents a compilation of research exploring different ways to apply corpus-based and corpus-informed approaches to English language teaching. Starting with an overview of research in the field of corpus linguistics and language teaching, various scenarios including academic and professional settings, as well as English as International Language, are described. Corpus-Based Approaches to ELT goes on to put forward several chapters focusing on error analysis using learner corpora and comparable native speaker corpora. Some of these chapters use translations and th.